DESIGN AND ANALYSIS OF A TRISULA T-SLOT MICROSTRIP ANTENNA FOR 5.8 GHZ FREQUENCY BAND - Hana Kamila Adiningtyas (Universitas Lampung, 2026)
Wireless communication technology based on radio waves enables more efficient information exchange in terms of cost and time. An antenna is one of the most important components in wireless communication systems. Microstrip antennas are widely used due to their compact size, light weight, and ease of fabrication; however, they generally suffer from narrow bandwidth. In this study, a trident-shaped T-slot microstrip antenna is designed to enhance the bandwidth at the 5.8 GHz frequency band. The antenna is fabricated on an FR-4 epoxy substrate with a relative permittivity of 4.4 and a thickness of 1.6 mm. The dimensions of the patch and T-slot are optimized using ANSYS HFSS. The simulation results show a bandwidth of 270 MHz, a return loss of −30.39 dB, a VSWR of 1.062, and a gain of 4.8 dB with a unidirectional radiation pattern. The measurement results indicate a bandwidth of 389 MHz, a return loss of −23.90 dB, a VSWR of 1.136, and a gain of 4.39 dB, also with a unidirectional radiation pattern. These results demonstrate that the trident-shaped and T-slot structure effectively improves the bandwidth of the microstrip antenna operating at 5.8 GHz.